STRATEGI PENGEMBANGAN EKOWISATA DI DESA RANTAU LANGSAT KABUPATEN INDRAGIRI HULU - Tika Riyanto; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
One of the efforts to optimally utilize local resources in RantauLangsat Village is to develop tourism with the concept of ecotourism, in this case the tourism carried out has an inseparable part with conservation efforts, local economic empowerment and encourage a higher sense of care for culture or culture. This underlies the difference between the concept of ecotourism and the conventional tourism model that has existed before. The purpose of this study is to see how the development strategy carried out by the Youth Sports and Tourism Office of IndargiriHulu Regency in developing ecotourism in RantauLangsat Village and what factors influence the development strategy carried out by the Youth Sports and Tourism Office of IndargiriHulu Regency in developing ecotourism in RantauLangsat Village. This research was located in RantauLangsat Village using qualitative descriptive methods and data collection techniques through observation, interviews and documentation. The results of this study prove that in developing ecotourism in RantauLangsat Village still has many obstacles, as well as inhibiting factors in developing ecotourism, namely resources (budget), human resources, facilities and infrastructure as well as community participation. Keywords: Strategy, Development, RantauLangsat, Youth Sports and Tourism Office